(untitled) (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 87-93 to 91-97. Investigation during T. Aus 2012 through Boro 2013-14 at BRRI farm, Gazipur evaluated the effect of magic growth (MG) solution on rice. The experiment compared variable doses of N with or without MG along with N control in a randomized complete block design with three replications. Basal application of N with its top dress was also compared with only top dress of N (no basal). All the plots (except control) received a blanket application of phosphorus, potassium, sulfur and zinc. The application of MG spraying produced no yield advantage on rice grain yield in Aus, Aman and Boro seasons. Basal application of N with top dress produced higher yield over N top dressing only in Boro season at lower rate of N. Bangladesh Rice j. 2015, 19(2): 91-97